(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
The greater and lesser cornua of the hyoid bone fuse with the body at a certain age. The fusion of hyoid bone can be helpful in estimating the age of unknown dead bodies. Several investigations have shown considerable variations in the age of fusion of hyoid bone. This study was aimed at examining the age of fusion of hyoid bone in population of Haryana. Also it was designed to assess whether fusion of hyoid is sex dependent. The sample comprised hundred (equal number of male and female) healthy hyoids bones. The hyoid bones were obtained from subjects, aged between 20-70 year, in consecutive autopsies. The X-ray films were examined for the presence of fusion between the greater and lesser cornua with the body. The statistical analysis of the data was done using SPSS program for windows. The significance of the data was verified using Chi-square test, Student’s t-test and ANOVA. The significance was predetermined at p<0.05. The mean age of unilateral fusion of greater cornua in females and males were 42.67 and 45.20 years respectively while mean age of bilateral fusion were 57.40 and 59.77 years in females and males respectively. The mean age of unilateral fusion of lesser cornu in females and males were 58.00 years and 59.00 years respectively while mean age of bilateral fusion were 63.67 years and 64.23 years in females and males respectively. It was seen from the present study that the mean age of fusion did not significantly differ in the two sexes. Fractures of hyoid when found in subjects below 45 years should be evaluated more carefully. Attempt to estimate age from hyoid fusion in Indians would be unreliable owing to the regional variations.